The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1016/j.stem.2017.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic Induction of Vasorin Regulates Notch1 Turnover to Maintain Glioma Stem-like Cells

Abstract: Tumor hypoxia is associated with poor patient survival and is a characteristic of glioblastoma. Notch signaling is implicated in maintaining glioma stem-like cells (GSCs) within the hypoxic niche, although the molecular mechanisms linking hypoxia to Notch activation have not been clearly delineated. Here we show that Vasorin is a critical link between hypoxia and Notch signaling in GSCs. Vasorin is preferentially induced in GSCs by a HIF1α/STAT3 co-activator complex and stabilizes Notch1 protein at the cell me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
182
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 146 publications
(189 citation statements)
references
References 72 publications
6
182
1
Order By: Relevance
“…It has been proposed that a common gene expression program underpins both cancer and stemness. Consistent with this hypothesis, it has been shown that STAT3 is required to maintain stemness in many different tumors [34,35,[64][65][66][67][68][69][70][71][72][73][74][75][76][77]. At least in breast cancer, a critical mechanism stimulated by STAT3 to regulate stemness involves genes in fatty acid oxidation [72,73] and the ability of STAT3 to adjust the ROS levels produced in mitochondria [73].…”
Section: Reprogramming and Stemnessmentioning
confidence: 90%
“…It has been proposed that a common gene expression program underpins both cancer and stemness. Consistent with this hypothesis, it has been shown that STAT3 is required to maintain stemness in many different tumors [34,35,[64][65][66][67][68][69][70][71][72][73][74][75][76][77]. At least in breast cancer, a critical mechanism stimulated by STAT3 to regulate stemness involves genes in fatty acid oxidation [72,73] and the ability of STAT3 to adjust the ROS levels produced in mitochondria [73].…”
Section: Reprogramming and Stemnessmentioning
confidence: 90%
“…Huang et al ., found that VASN‐containing exosomes promoted the migration of recipient human umbilical vein endothelial cells (HUVECs) . Recently, a report reveal that VASN is critical to maintaining glioma stem‐like cells in hypoxia . However, the role of VASN in cancer remains enigmatic.…”
Section: Introductionmentioning
confidence: 99%
“…12 Recently, a report reveal that VASN is critical to maintaining glioma stem-like cells in hypoxia. 13 However, the role of VASN in cancer remains enigmatic.…”
Section: Introductionmentioning
confidence: 99%
“…Niches provide exclusive habitat where stem cells propagate continuously in an undifferentiated state through self-renewal 5 . GSCs are dispersed within tumors and methodically enriched in perivascular and hypoxic zones 11,12,13 . GSCs essentially received positive signals from endothelial cells and pericytes, such as ligand/receptor triggers of stemness pathways and adhesion components of the extracellular matrix 13,14,15,16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…GSCs essentially received positive signals from endothelial cells and pericytes, such as ligand/receptor triggers of stemness pathways and adhesion components of the extracellular matrix 13,14,15,16,17 . They are also protected in rather unfavorable conditions where their stemness traits resist hypoxic stress, acidification, and nutrient deprivation 11,12,18 . Recently, it has been suggested that this latter capacity is linked to the function of the RNA binding protein QKI in the down-regulation of endocytosis, receptor trafficking and endo-lysosome-mediated degradation 18 .…”
Section: Introductionmentioning
confidence: 99%